Structural Characterization, Antimicrobial, Antibiofilm, Antioxidant, Anticancer and Acute Toxicity Properties of N-(2-hydroxyphenyl)-2-phenazinamine From Nocardiopsis exhalans (KP149558) - Ramalingam, Vaikundamoorthy; Rajaram, Rajendran; Archunan, Govindaraju; Padmanabhan, Parasuraman; Gulyás, Balázs (Frontiers in Cellular and Infection Microbiology, 2022)
The present study aimed to isolate and identify potential drugs from marine actinomycete Nocardiopsis exhalans and screen them for biomedical applications. The cell-free culture of N. exhalans was extracted with ethyl acetate and the solvent extract showed six fractions in thin-layer chromatography. The fractions were subjected to column chromatography for purification and evaluated for activity against human clinical pathogens. Fraction 4 showed significant activity and was identified as N-(2-hydroxyphenyl)-2-phenazinamine (NHP) using spectral analyses. Further, the NHP showed excellent biofilm inhibitory activity against human clinical pathogens E. coli, P. aeruginosa, and S. aureus. The in vitro antioxidant activity confirmed that NHP is scavenging the oxidative stress-enhancing molecules. The anti-proliferative activity of NHP against human breast cancer cells showed significant activity at 300 µg/ml and less cytotoxic activity against normal cells. Additionally, the toxicity assessment against zebrafish revealed that NHP does not cause any toxicity in the important organs. The results highlight N. exhalans as a promising candidate for the development of antibiotics with potential therapeutic applications.